Avaliação dos efeitos antioxidantes do extrato de Annona crassiflora Mart. e seus polifenóis em miocárdio de camundongos hiperlipidêmicos - Komino, Eliana Akemi (2022)
Dyslipidemia and oxidative stress have a straight relation in pathogenesis of cardiovascular diseases. Annona crassiflora Mart. (ACM) has been used to treat inflammation and pain in folk medicine, being this plant a source of polyphenols presenting a high antioxidant capacity. In the present study, the antioxidant properties of ACM were elucidated in hyperlipidemic (HLc) mice model induced by intraperitoneal injection of Triton WR-1339 under oral administration of crude extract (CEAc) or polyphenol enriched fraction of ACM fruit peel. Principal component analysis and Pearson's correlation revealed positive asociations between blood and fecal biochemical data with cardiac oxidative stress biomarkers. Here, CEAc was able to increase the reduced glutathione content (GSH) and reduce the enzimatic activities of superoxide dismutase (SOD), catalase (CAT) and glutathione peroxidase, when compared to the vehicle group without treatment. The polyphenols-rich fraction from CEAc was able to enhance the total antioxidant capacity, the GSH content, SOD and CAT enzimatic activities, comparing to vehicle group. Moreover, this fraction decreased carbonyl content, lipid peroxidation and glutathione reductase and glucose-6-phosphate dehydrogenase enzimatic activities, also comparing to vehicle group. ACM fruit peel showed improvement in glutathione system, mainly when used polyphenol enriched fraction, indicating a potential cardioprotective antioxidant usage of this plant extract.